Inaccuracies enrooted in the attribution and classification of coins of the Cilician Armenian Kingdom Part II Revisiting the copper coinage of Levon IV - Vardanyan, Ruben (ARAMAZD: Armenian Journal of Near Eastern Studies, 2019)
At present, seven groups of copper coins are attributed to Levon IV (1320-1342), the king of Cilician Armenia. However, iconographic, stylistic and metrological differences have been observed in these coins that make the possibility of attributing them all to the same king doubtful. A comparative study shows that only two of these groups can be attributed with confidence to Levon IV. These are the small copper coins (Group VI, Figure 22 and Group VII, Figure 23), which are a coherent continuations of Oshin’s copper coinage. The minting of such small copper coins continued under the two kings who followed Levon IV: Ki (Guy) and Kostandin III (Figure 35). As for the other groups, two of them (Groups I and II, Figures 17 and 18) belong to Levon III as they are closely linked to Kostandin I’s coins by iconography and style. Preliminary observations were made on the other three groups. Issues of their dating and attribution will be further examined in one of the following articles in this series.